Burial traditions in early Mid-Holocene Island Southeast Asia: new evidence from Bubog-1, Ilin Island, Mindoro Occidental. (August 2019) - Pawlik, Alfred; Crozier, Rebecca; Fuentes, Riczar; Wood, Rachel; Piper, Philip
Abstract: Abstract : The Bubog-1 rockshelter on Ilin Island has provided important evidence for Late Pleistocene to Mid-Holocene ( c. 33 000–4000 cal BP) human habitation, yet little is known about the contemporaneous transmission of material culture, technology and mortuary practices across Island Southeast Asia. Recent archaeological research at Bubog-1 has revealed a tightly flexed inhumation dating to c. 5000 cal BP—a type representative of a widespread, contemporaneous burial practice observed across the region. The emergence of diverse burial practices and their spread across Island Southeast Asia coincides with evidence for technological innovation and increasing long-distance interaction between island communities.